Kontribusi Sagu (Metroxylin Sp) Terhadap Ketahanan Pangan Pokok Rumah Tangga Desa Labela Kabupaten Konawe - Rizka, Syahria; Ma'mun, Sitti Rahma; Asis, Patta Hindi; Ma'mun, Sitti Zakiah; Rosmalah, Sitti (Agrisurya, 2024)
This research aims to analyze the contribution of sago and household staple food security in Labela Village, Besulutu District, Konawe Regency. There were 40 households as samples and were obtained using a simple random sampling method to determine the sample studied. Data collection uses primary and secondary data methods. Data analysis is calculating income and frequency of sago consumption using the contribution formula. To analyze household food security, the HFIAS (Household Food Insecurity Access Scale) measurement method was used and to measure food diversity, the HDDS (Household Dietary Diversity Score) method was used. To determine the level of difference between sago and rice consumption, a one-sample t-test statistical analysis was used. The results of this research are that the average household income in Labela Village is IDR. 3,160,000.00 from agriculture and IDR. 2,970,000.00 non-agricultural income. The food security analysis consists of 4 categories, namely 20% of households are food insecure, 17% are mildly food insecure, 28% are moderately food insecure, and 35% are severely food insecure. The results of food diversity consist of 3 categories, namely 45% of low food diversity households (food groups 1-6), 37% medium food diversity (food groups 7-12), and 18% high food diversity (food groups 13-16). The contribution of sago, namely 40%, shows that sago is included in the medium contribution and the results of the T-test analysis show a significance value of 0.000 < 0.05, there is a correlation between sago consumption and rice as the family's staple food. Key words: HFIAS, HDDS, food security, household, sago